The Universal Loves in Maulana Rumi’s Poems (Semiotics Theory by Roland Barthes) - Diana, Eli; Lestari, Mei Winda (JURNAL LITERARY CRITICISM, 2018)
Human are social creatures because they interact and communicate a language that they can understand each other. Until they can create social communities. In human life there are many kinds of mysterious in their surrounding such as sign, symbol, word or sentences that had meaning inside. The purpose of this research to describe how the semiotics applied in Maulana Rumi’s poems and to know the meanings of Maulana Rumi’s poems viewed from semiotics theory. The researcher used qualitative research method to analysis the data. The data analyzed  of 10 poems, the titles are, the spirit and body, the spirit ruby, the great wagon, love is the way massagers, Imra’u’L’QAYS, no flag, eyes, the death of Saladin, the many wines & quietness. The result of analyzed data based on applied five codes as follow, hermeneutic code, proareitic code, semantic code, symbol code & culture code. These poems full of the anigma and meanings. Therefore, the anigma and was arranged the beauty words in each stanza those made Rumi’s poems being more wealth of art.   Keywords: Maulana Rumi, poems, semiotics, universal loves